WAKAF UANG SEBAGAI PENGEMBANGAN PEREKONOMIAN MASYARAKAT DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM NASIONAL: WAKAF UANG SEBAGAI PENGEMBANGAN PEREKONOMIAN MASYARAKAT DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM NASIONAL - Aeni, Desri Nurul; Yunianto, Aditya; Jaenudin, Jejen; Fauzi, Muhammad Ridwan; Farhana, Nurulita (Al-muamalah, 2023)
ABSTRACT According to the executive director of KNEKS, "The potential for cash waqf in Indonesia is huge, reaching 180 trillion every year, however, the development of cash waqf in Indonesia is still low, as seen from BWI data, the cash waqf collected until 2020 reached IDR 391 billion, even though the potential for annual waqf reached IDR 180 trillion”. This research aims to determine the potential of cash waqf as a community economic development. The research method used in this research is a literature study with a normative approach. This research shows that waqf can produce various profits and benefits. The profits generated can finance important sectors in need such as Health, Education, and even the domestic business sector. Now, it's just a matter of how this opportunity is utilized in a synergy between government, institutions, and society itself. Cash waqf has an important role in the community economy and the wakif itself, where its management is carried out by nadzir through LKS-PWU.